2013
DOI: 10.1590/s0044-59672013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do tratamento com formalina e sulfato de cobre sobre os parâmetros hematológicos e parasitos monogenéticos em juvenis de Hemigrammus sp. (Osteichthyes: Characidae)

Abstract: RESUMOO objetivo deste trabalho foi avaliar a eficácia da formalina e sulfato de cobre no controle de monogenéticos em juvenis de Hemigrammus sp e seu efeito na contagem diferencial de leucócitos. Utilizou-se um delineamento inteiramente casualizado com 5 tratamentos e 3 repetições. Todos os tratamentos tiveram duração de três dias e corresponderam a: T1, controle; T2 e T3 banho por imersão de uma hora em formalina, em duas concentrações uma de 0,25 ml e outra 0,1 ml formalina L ). Após o período experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…In contrast, other studies reported that the use of formalin caused increased pH and reduced concentration of dissolved O 2 in the water (Treves-Brown, 2000;Martins, 2004). These changes were not found here, corroborating the findings of other studies (Fajer-Ávila et al, 2003;Sitjà-Bobadilla et al, 2006;Pahor-Filho et al, 2012;Paixão et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, other studies reported that the use of formalin caused increased pH and reduced concentration of dissolved O 2 in the water (Treves-Brown, 2000;Martins, 2004). These changes were not found here, corroborating the findings of other studies (Fajer-Ávila et al, 2003;Sitjà-Bobadilla et al, 2006;Pahor-Filho et al, 2012;Paixão et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…No mortality of A. gigas was observed whatsoever during the 1 h and 12 h therapeutic baths with formalin, since the lethal concentration for this fish was previously determined. In contrast, Paixão et al (2013) found 100% and 66.6% mortality for Hemigrammus sp. exposed to 275 and 110 mg L − 1 formalin during 1 h, respectively.…”
Section: Parametersmentioning
confidence: 86%
See 2 more Smart Citations
“…According to Martins (2004), 37% formaldehyde can be used in the form of a short bath (up to 60 min) in the concentration of 55.5 mg/L to 92.5 mg/L and in long-term baths (24 h) at a concentration of 3.7 mg/L to 5.55 mg/L. However, Paixão et al (2013) working with these concentrations with the fish species Hemigrammus (a characid widely used in aquariums) using formaldehyde baths for 60 minutes reported 100% mortality. The authors suggest that this may have been due to the fact that wild fish are more susceptible to stress and less rustic than those in cultivation.…”
Section: Discussionmentioning
confidence: 99%